A scoping review of African natural products against gastric ulcers and Helicobacter pylori. (30th January 2023) - Dinat, S.; Orchard, A.; Van Vuuren, S.
Abstract: Ethnopharmacological relevance: African traditional medicine is one of the oldest and most diverse practices for treating ailments and numerous natural products have been recommended for gastric ulcer treatment. Helicobacter pylori is the main causative organism implicated in several diseases, most notably in causing inflammation and the onset of gastric ulcers. Current H. pylori treatment methods are losing efficacy as H. pylori rapidly gains resistance to antibiotics. Hence, a search into natural products and their historical traditional efficacy for the treatment of gastric ulcers is of interest. Aim of the study: This review aimed to summarise the African use of natural products, including medicinal plants noted in ethnobotanical reviews, used traditionally to treat gastric ulcers, and highlights the investigations into the anti- H. pylori activity of medicinal plants and bee products found in Africa. Methodology: A systematic review was carried out to identify natural products, including those used traditionally in Africa to treat gastric ulcers, and to correlate this with scientific investigations into the anti- H. pylori activity of natural products used in Africa. Results: A total of 107 literature sources describing the traditional use of medicinal plants in gastric ulcer treatment were found, from which 360 medicinal plants were identified. Of the plants used traditionally for gastric ulcer treatment, 11% were investigated either in vitro or in vivo for anti-ulcer and anti- H. pylori activity. Of the 122 medicinal plants eliciting antimicrobial or anti-ulcer activity, Hibiscus sabdariffa L. calyx extract and Terminalia macroptera Guill. & Perr. root extract were found to have the most noteworthy antimicrobial activity, with minimum inhibitory concentrations (MICs) of 0.01 mg/mL and 0.03 mg/mL respectively. The essential oils of Piper longum L. and Pachira aquatica Aubl. displayed the most notable in vitro anti- H. pylori activity (MIC of 0.01 mg/mL and 0.02 mg/mL). Several in vivo studies found medicinal plant extracts effective in reducing the H. pylori load along the gastric mucosa. The South African honey variants, Pure Honey and Champagne Royal Train (common names given by supplier) were the most antimicrobially effective (MIC of 0.01–10.0%, 0.63–10.00% v/v) in inhibiting H. pylori when assessed in vitro. Conclusion: These results highlight the potential of natural products to inhibit H. pylori growth and serve as a possible stepping-stone in understanding the management of ulcers. Furthermore, effective natural product treatment or prophylactic use for preventing H. pylori growth may provide a more affordable option for African populations. Graphical abstract: Image 1